STRENGTHS AND DIFFICULTIES OF NATIVE AND NON-NATIVE SPEAKING ENGLISH TEACHERS: PERSPECTIVES FROM THE ENGLISH LANGUAGE CLASSROOM IN ISRAEL - ELIZABETH KARVONEN; VASILE CHIS (Studia Universitatis Babes-Bolyai, 2013)
ABSTRACT. Native English speakers are often assumed to be the most desirable English teachers, due to their fluency and superior knowledge of the language. However, recent research has shown that this is not necessarily the case, especially regarding novice teachers in their first year of teaching. This research recorded and analyzed the experiences of thirty novice teachers, teaching English as a foreign language (EFL). All teachers were graduates of the same training program, yet when asked to rate how they coped during their first year in the classroom in various spheres such as planning, assessment or classroom management, the native English speaking teachers showed that they coped less well than their non-native speaking peers in all spheres. This article discusses the topic from various angles and identifies fundamental reasons why the native speaking English teachers' apparent advantage might also prove to cause specific difficulties.